Aquisição da linguagem escrita de alunos com deficiência intelectual: o uso de jogos pedagógicos na sala de recurso multifuncional - Gadelha, Francisca Geruza (2014)
This research study examined whether the use of educational games in one of Multifunctional Room collaborates to students with intellectual disabilities to learn the written language. Our theoretical foundation has authors like Kishimoto (2011a; 2011b; 2008), Moyle (2006) and Brougère (1998; 2008) and researches made by Vygotsky (1983; 2004; 2007; 2008) and Piaget (1978) on the development and human learning. For studies about the acquisition of written language researched studies of the authors and Teberosky Blacksmith (1999); Vygotsky (2007) and Mitchell (2005; 2012). The methodological procedures used was the qualitative research intervention. Data were collected through visits and coordinated by the researcher in a room multifunctional features in a public school in the city of Fortaleza. Were made 36 visits with three people and 12 moments of language games with each person. The survey results indicated a conceptual advancement of all people in the acquisition of written language. The presence of the researcher contributed to a social interaction, to the speed of internal processes and allowed the evolution of the people to understand the alphabetic writing system. We conclude that the use of educational games in SRM is a resource facilitator of learning written language, promotes internal processes and allows the conceptual evolution of writing from people who have intellectual disabilities language.